Comparison of Dysphagia Between Infratentorial and Supratentorial Stroke Patients - Yong Kyun Kim; Jung Hyun Cha; Kyun Yeon Lee (Annals of Rehabilitation Medicine, 2019)
Objective To compare dysphagia between infratentorial stroke patients and supratentorial stroke patients. Methods Subjects of this study were patients with post-stroke dysphagia (PSD) who were admitted to our medical institution between May 2014 and June 2017. We evaluated a total of 64 patients with PSD. A videofluoroscopic swallowing study (VFSS) was performed to determine dysphagia severity. We measured the following parameters: pharyngeal transit time (PTT), post-swallow pharyngeal remnant, Penetration Aspiration Scale (PAS) scores, and Functional Dysphagia Scale (FDS). We analyzed patient’s results from VFSS performed at admission. All VFSS images were recorded using a camcorder running at 30 frames per second. An AutoCAD 2D screen was used to measure post-swallow pharyngeal remnant. Results In this study, PTT and FDS were similar (p>0.05) between infratentorial stroke patients and supratentorial stroke patients. However, there were significant differences in pharyngeal remnant and PAS scores between the two groups (p<0.01 and p<0.05, respectively). Conclusion Both pharyngeal remnant and PAS score registered higher levels from VFSS test for infratentorial stroke patients than those for supratentorial stroke patients. This suggests greater chances of problems occurring with swallowing, the major functions of pons. Thus, clinicians should pay particular attention to active dysphagia evaluation and treatment in PSD of infratentorial stroke patients.